PEMBERDAYAAN KADER POSYANDU DALAM STIMULASI DETEKSI DAN INTERVENSI DINI TUMBUH KEMBANG (SDIDTK) PADA BALITA DAN ANAK PRA SEKOLAH DI POSYANDU MELATI DESA BUKIT KRATAI WILAYAH KERJA UPT BLUD PUSKESMAS RUMBIO - Syahda, Syukrianti; Nislawaty, Nislawaty (COVIT (Community Service of Tambusai), 2021)
The coverage of health services for infants and children under five, one of which is the Stimulation of Detection of Early Developmental Interventions (SDIDTK) at the Riau Province level is still low at 87.8%, which is below the set target of 90%, while for Kampar Regency it is far below, namely 77% including Bukit Kratai Village Working Area of UPT. Rumbio Health Center BLUD. SDIDTK conducted at the Posyandu only carried out weighing, measuring height, and body circumference only. Posyandu cadres have not been able to carry out comprehensive early detection and early intervention on developmental deviations of toddlers. Posyandu health cadres have never attended SDIDTK training. This Community Service (PKM) activity aims to empower posyandu cadres in Bukit Kratai Village. Therefore, improving education for cadres related to SDIDTK is needed to increase the quantity and quality of services at this posyandu. The task of posyandu cadres is very important and where posyandu activities should not only monitor growth but also monitor developments so that they can detect deviations in growth early. Thus, the growth and development of children through detection of growth and development is part of the task of posyandu cadres to detect early developmental delays in children.